Representasi Peran Perempuan dan Kesetaraan Gender dalam Iklan Skincare Forebie - Muhammad Adnan Sukhfi; Rafi Hadrian Pratista; Erwan Sudiwijaya (Universitas Muhammadiyah Klaten, 2025)
Abstract This study examines the representation of women's roles and gender equality in Forebie skincare advertisements on social media platforms, particularly Instagram and TikTok. While women's representation in advertising has historically been constrained by gender stereotypes, the emergence of feminism and